2017
DOI: 10.18502/kls.v3i6.1159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sappan Wood Extract (Caesalpinia sappan), Wheat grass and Vitamin E Treatment on the Liver Structure of Iron overload of Rat (Rattus norvegicus)

Abstract: This research was carried out to detect the effect of Sappan Wood Extract (Caesalpinia sappan), Wheat grass and Vitamin E Treatment on the liver structure of iron overload rat (Rattus norvegicus).The method of experimental used Completely Random Design (CRD in triple repetition. The treatment had been carried out orally. Iron dextran with total dose of 1.5 g kg −1 of body were given to rat on the first, fourth, seventh, ten and thirteenth day. Sappan Wood Extract (Caesalpinia sappan)200 mg kg −1 bw, 400 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Flavonoids and brazilin make Sappan wood a good candidate as an iron-chelating agent. Based on in vivo testing, SWEE was able to reduce iron in the blood and improve the function of rat livers with excessive iron [8][9][10]. This study performed a cell viability test using SWEE, but further testing is needed to determine the ability of SWEE to act as an iron chelator in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids and brazilin make Sappan wood a good candidate as an iron-chelating agent. Based on in vivo testing, SWEE was able to reduce iron in the blood and improve the function of rat livers with excessive iron [8][9][10]. This study performed a cell viability test using SWEE, but further testing is needed to determine the ability of SWEE to act as an iron chelator in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in ferritin indicated that sappan wood extract has the ability to chelate the iron. Research has tested the use of sappan wood ethanol extract (SWEE) as an iron chelator in vivo using rats, where SWEE reduced iron in the blood and improved the function of rat livers with excessive iron accumulation [8][9][10]. However, further investigation is necessary to investigate the toxicity of SWEE in the target organ.…”
Section: Introductionmentioning
confidence: 99%
“…C. sappan L. is distributed in Southeast Asia, and its dried heartwood has been used as a traditional ingredient in foods or beverages and has a wide variety of medicinal properties. 94 In Indonesia, its material has long been used in folk medicine to treat tuberculosis, diarrhea, dysentery, skin infections, anemia, detoxification, syphilis treatment, an antiseptic to stop bleeding, and pain due to blood circulation disorders. 95 …”
Section: [450] Spirocyclic System (D)mentioning
confidence: 99%
“…Kayu ini memiliki banyak khasiat dan secara turun temurun dijadikan sebagai minuman tradisional atau tambahan warna pada air minum konsumsi sehari-hari hingga saat ini. 3 Kayu Sepang banyak mengandung flavonoid dan polifenol yang berpotensi mereduksi radikal bebas dan mencegah terbentuknya spesies oksigen reaktif serta menghambat aktivitas enzim xantin oksidase serta mengkatalisis pembentukan radikal superoksid dengan aktivitas 89,9% 4,5 dalam mencegah kanker, diabetes, shock, arthritis serta percepatan proses penuaan. 6 Tanin dan flavonoid merupakan senyawa fenol, yang berperan sebagai inhibitor bagi pertumbuhan mikroba karena mampu mendenaturasi protein serta merusak dinding sel bakteri.…”
Section: Pendahuluanunclassified